2020
DOI: 10.1080/13102818.2020.1719020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LcGAPC and its transcriptional response to salt and alkali stress in two ecotypes of Leymus chinensis (Trin.) Tzvelev

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a housekeeping protein which plays various roles in non-metabolic processes in addition to its role in glucose catabolism. There are several GAPDH isoforms in plant cells. In this study, we cloned the full-length cDNA encoding the isoform GAPC in two ecotypes of Leymus chinensis (Trin.) Tzvelev, gray-green type and yellow-green type. The LcGAPC sequence includes an open reading frame (ORF) of 1014 bp encoding 337 amino acids. The predicted molecular weight is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Therefore, these genes might have similar functions. GapC-type genes have been shown to participate in plant responses to heat, anaerobic conditions, salt and drought (Yang et al 1993;Lu et al, 2020;Kappachery et al 2015). Other studies also demonstrated that GapC-type genes play important roles in helping plants withstand abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these genes might have similar functions. GapC-type genes have been shown to participate in plant responses to heat, anaerobic conditions, salt and drought (Yang et al 1993;Lu et al, 2020;Kappachery et al 2015). Other studies also demonstrated that GapC-type genes play important roles in helping plants withstand abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…ThGAPB can reduce the production of ROS by maintaining a high recycling rate of ADP and NADP + , helpful for the maintenance of photosynthetic efficiency and development of plants under saline conditions, as it can improve the salt tolerance of plants (Chang et al 2015). The LcGAPC gene is highly expressed in the two ecotypes of Leymus chinensis under longterm and high-concentration NaCl stress (Lu et al 2020). PsGAPDH from oyster mushroom has been transferred into rice, and seedlings of this transgenic rice are significantly better than the wild type in growth and germination under salt stress (Lim et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that the overexpression of HXK1 increases tolerance by regulating NHX1 gene expression to salt stress in Malus domestica , similarly, GAPC helps in NaCl stress tolerance by acting as sensor for H 2 O 2 in Leymus chinensis [ 126 , 127 ]. Reports showed that the carbohydrates are not only used to adjust the osmotic balance but also play an important role as protective agents in plants to regulate homeostasis under salt stress [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there are two ecotypes of L. chinensis, namely, gray-green (GG) and yellow-green (YG), which differ in their survival strategies. GG has a wider distribution and is more resistant to salt stress compared with YG (Zhou et al, 2014;Lu et al, 2020). Thus, differences in L. chinensis ecotypes may reflect adaptive evolution (Kawecki and Ebert, 2004;Savolainen et al, 2007;Delker et al, 2010;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%